AIR QUALITY MONITORING AND STRATEGY IN INDONESIA - P.L. Coutrier; Saut M. Lubis; Noegroho Hadi (Testing Center for Oil and Gas LEMIGAS, 1994)
BAPEDAL, The Environment Impact Management Agency is responsible for the air pollution control. In addressing the air pollution BAPEDAL launched the